Access and Influence of the Guidance Office on The Student’s Emotional Needs - Santos, John Mark S.; Dadez, Mark Joseph G.; Santos, John Vincent Llenada (EDUCATIO : Journal of Education, 2023)
This study seeks to identify and resolve a variety of issues that students face, including not only their physical behaviors but also their emotional feelings. The study focuses on students' emotions, especially during the pandemic, when many of them are dealing with difficulties that cause stress or uncertainty, and have become a major source of depression, which has been alarming at times. Most students do not go to the guidance office because they are embarrassed or afraid that if other students see them, they will start talking about it. The study also intends to investigate some of the more serious reasons why students keep their problems to themselves rather than seeking assistance or advice from a guidance counselor, determining whether they had encountered more difficulties with Holy Cross College students' emotional problems that resulted in difficult circumstances. Identifying the number of students in the school population who are dealing with difficult situations that are causing them to lose focus in their studies. Respondents will be all third-year college students enrolled at Holy Cross College in Santa Rosa, Nueva Ecija for the academic year 2021-2021. Examining the study's findings, it can analyze and evaluate that data to gain a better understanding of how the guidance counselor comforts and helps students, particularly those who have stopped studying due to their circumstances, but they don't need to be stopped or do things they don't want to do if the guidance counselor comforts and helps them.